Metrics for Large-Scale Agile Development: A Survey of the Brazilian Software Industry - Menezes, Renato; Marinho, Marcelo; Sampaio, Suzana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Managing large agile projects that extend beyond a single software development team is challenging due to the diverse set of influencing factors. In such a flexible and dynamic environment, it is crucial to perform appropriate measurements tailored to each specific reality and objective to promote continuous improvement and monitor progress effectively. This paper presents the results of a survey conducted within the industry involving a sample of 145 professionals from the Brazilian large-scale software market. The research draws on knowledge from literature sources to outline and discuss participants’ perceptions of the scaled agile environments in which they operate. It analyzes current practices in metric selection strategies, the stakeholders using these measurements, the objectives behind their use, adoption trends, and the resulting impacts.